Delay in design phase in Malaysia construction : the cause and the factor to reduce the delay - Noor Syazwani, Mohd Rizhuan (2019)
Construction delay is anything that impedes the ability of a certain obliged party to maintain a schedule. Delays manifest during all project phases, where they might initiate even in the design phase. Delays in the planning and design phases for construction projects were literally in a critical state. While most studies focus on finding causes or resolving delay problems in the construction phase, few studies had analysed delay problems in the planning and design phases. Hence, this research aims to study indepth about design phase, their causes, and the possible strategies to reduce delays in the planning and design phases. Meanwhile, an online questionnaire was also distributed to private consultants in order to get a clearer vision of this problem. Relative importance index (RII) analysis methods were adopted to rank delay causes in terms of their severity as perceived by the respondents. Changes in clients’ requirements, poor scope definition and miscommunication were among the most critical causes of delay in the planning and design phases. The communication aspect could have been the principal key strategy to resolve some major delay causes, in the effort to mitigate delays in the planning and design phases, as well as in the construction phase.